Development of the ‘Tangga Kesantunan’ Board Game as a Civic Education Learning Medium to Instill Politeness Values in Third-Grade Elementary School Students - Triya Abida Kolis; Fienna Saadatul Ummah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The decline in polite behavior in elementary school students is one of the problems that needs attention in PPKn learning. This study aims to develop the board game media